The 35-d modulation of the X-ray emission of Her X-1 in the framework of the SOD model: results of a three-dimensional SPH simulation - Lanzafame, G.; Belvedere, G.; Molteni, D. (Monthly notices of the Royal Astronomical Society, 1994)
Several models have been proposed to explain the 35-d X-ray periodicity observed in Her X-1. We present the results of six three-dimensional quasi-polytropic smoothed particle hydrodynamics (SPH) simulations of the tilted, twisted accretion disc of Her X-1 carried out in the light of Roberts’ slaved orienting disc model (SOD) with the intention of finding some limits to the inclination of the rotation axis of the secondary and to the value of the polytropic index γ. These results show that a γ value between 1.05 and 1.1 and an inclination angle ϕ of the order of 45° are the most suitable for enabling the SOD model to work in three-dimensional space. The simulated disc is rather small and thin, and its precessional motion is reproduced in a satisfactory way. Nevertheless, our simulations seem to be unable to explain the 35-d period shadowing effect of Her X-1, because of the too-uniform temperature distribution in the disc. This does not preclude the validity of the SOD model, as the results concerning the temperature distribution are obtained in the quasi-polytropic approximation, although temperature profiles in good agreement with the analytical models have already been obtained in our previous simulations. Our results may, however, suggest alternatively that a non-processing disc whose optical depth is subject to a long-period variation may account for the observed 35-d period X-ray modulation. In any case, implementation of the radiative terms should be taken into account in future more stringent tests of the model.